Ellagic acid affects mRNA expression levels of genes that regulate cholesterol metabolism in HepG2 cells. Issue 5 (4th May 2019) - Kubota, Shizuka; Tanaka, Yuma; Nagaoka, Satoshi
ABSTRACT: Ellagic acid has been shown to improve cholesterol metabolism in animal studies, but the molecular mechanisms underlying this function have not been fully understood. We performed DNA microarray analysis to elucidate the effects of ellagic acid on cholesterol metabolism in HepG2 hepatocytes. This revealed that the expression levels of several genes related to cholesterol metabolism, including the low-density lipoprotein receptor (LDLR), were changed by ellagic acid treatment. Using a real-time PCR and immunoblot we confirmed that ellagic acid treatment up-regulated mRNA and protein expression level of the LDLR. Moreover, In the presence of 25 μM ellagic acid, extracellular apoB protein and MTP mRNA levels were significantly decreased. These findings indicate that ellagic acid improves cholesterol metabolism through the up-regulation of LDLR, down-regulation of MTP mRNA and reduces extracellular apoB levels. The ellagic acid-induced up-regulation of LDLR occurred via the extracellular signal-regulated kinase (ERK) signaling pathway in HepG2 hepatocytes. Abbreviations: LDLR: low-density lipoprotein receptor; apoB: apolipoprotein B; PKC: diacylglycerol-protein kinase C; MAPK: mitogen-activated protein kinase; ERK: p42/44 extracellular signal-regulated kinase; JNK: c-Jun N-terminal kinase; VLDLR: very low density lipoprotein receptor; PPARδ: peroxisome proliferator-activated receptor δ; SREBPs: sterol regulatory element-binding proteins; MTP: microsomal triacylglycerol transfer protein; LPDS: lipoprotein-deficient serum Graphical abstract: : Ellagic acid induces an up-regulation of LDL receptor via the extracellular signal-regulated kinase (ERK) signaling pathway in HepG2 hepatocytes.